Diagnosis of an Umbilical Vein Aneurysm at 30 Weeks Gestation - Meredith S. Campbell; Amanda M. Craig; Jeff Reese; Alicia K. Crum; Soha S. Patel (Case Reports in Obstetrics and Gynecology)
Background. Fetal umbilical vein aneurysm is an uncommon anomaly without clear guidelines regarding the management of these pregnancies. Case Presentation. We describe an ultrasound diagnosis of this condition involving a 38-year-old multigravid woman who presented at 30 weeks and 3 days gestation with severe fetal growth restriction, reverse end-diastolic flow on umbilical artery dopplers, elevated ductus venosus doppler, and an umbilical vein aneurysm. Due to nonreassuring fetal assessment in the setting of an umbilical vein aneurysm, she underwent a cesarean delivery with a favorable neonatal outcome. Conclusions. There are currently no guidelines for the management of an umbilical vein aneurysm. This case demonstrates a successful multidisciplinary approach for creating a plan of care focused on achieving a favorable outcome for a fetus with a large umbilical vein aneurysm. The approach took into account timing of delivery given the potential for fetal morbidity and mortality, while factoring in the risk of prematurity.